Process for the preparation of hydrophobic polyvinylidene fluoride microporous filtration membranes

CN116059856BActive Publication Date: 2026-10-20NANJING TECH MEMBRANE APPLICATION TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211558627.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-06
Publication Date
2026-10-20
Estimated Expiration
2042-12-06

AI Technical Summary

Technical Problem

[0005]有鉴于此,本发明提供了一种疏水性聚偏二氟乙烯微孔滤膜的制备方法,本发明主要解决聚偏二氟乙烯滤膜在处理含油高盐废水时,膜易被油污垢等有机污染物污染,进而造成膜纯水通量低和膜寿命缩短的技术问题

Benefits of technology

[0023]1、经由上述的技术方案可知,与现有技术相比,本发明以聚偏二氟乙烯为主,在不改变膜本质不变情况,加入了聚氯乙烯和聚间苯二甲酰间苯二胺制备的疏水滤膜作为疏水层,然后在滤膜表面以MOF颗粒和磺基甜菜碱甲基丙烯酸酯紫外接枝聚合形成接枝聚合物,再通过静电纺丝工艺制备的纳米纤维层,疏水层和纳米纤维层二者合一构成具有亲/疏水复和结构的微孔滤膜,不仅显著提高含油高盐废水的分离效率,而且具有优异的耐污性和机械强度,延长了膜的使用寿命。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of microporous filter membrane material, and discloses a preparation method of a hydrophobic polyvinylidene fluoride microporous filter membrane.The hydrophobic filter membrane prepared by adding polyvinyl chloride and poly-m-phenylene isophthalamide into polyvinylidene fluoride as a hydrophobic layer without changing the nature of the membrane, and then a nanofiber layer formed by MOF particles and sulfobetaine methacrylate ultraviolet graft polymerization is constructed on the surface of the flat filter membrane, so that the microporous filter membrane with hydrophilic / hydrophobic complex structure is formed by the combination of the two, which not only significantly improves the separation efficiency of oil-containing high-salinity wastewater, but also has excellent dirt resistance and mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of microporous filter membrane materials technology, and in particular to a method for preparing hydrophobic polyvinylidene fluoride microporous filter membranes. Background Technology

[0002] High-salinity wastewater refers to wastewater with a salt content greater than 1% (>10g / L). It mainly originates from three sources: (1) industrial production processes; (2) direct seawater utilization in coastal areas; and (3) continuous salt accumulation during wastewater recycling. Currently, methods for treating high-salinity wastewater mainly include chemical sedimentation flocculation, biological methods, electrolysis, membrane methods, distillation, incineration, and evaporation crystallization. Among these, membrane technology has advantages such as high efficiency and energy saving, no phase change, compact equipment, and easy integration with other technologies, and has been widely used in the water treatment field in recent years. Hydrophobic membranes, as the core of hydrophobic membrane separation technologies such as membrane distillation, membrane absorption, membrane degassing, membrane extraction, and membrane emulsification, play an increasingly important role in wastewater treatment, seawater desalination, gas separation, and oil-water separation.

[0003] Polyvinylidene fluoride (PVDF) is more soluble in organic solvents than polyethylene, polypropylene, and polytetrafluoroethylene (PTFE), exhibits high processability, can be prepared via solvent-free phase separation, and possesses good chemical stability, thermal stability, and mechanical strength, making it a high-performance separation membrane material. (Patent document number: [omitted])

[0004] CN2012101320968 discloses a "Preparation Method of Hydrophobic Polyvinylidene Fluoride Microporous Filter Membrane". This patent method involves dissolving polyvinylidene fluoride polymer material in an organic solvent mixture, forming a primary membrane using rollers, and finally placing it in a water bath at 5-50℃ for final molding, followed by washing and drying to obtain the final product. While the polyvinylidene fluoride microporous filter membrane prepared by this method is hydrophobic, the PVDF membrane material exhibits poor antifouling properties when treating oily and high-salt wastewater, leading to severe membrane fouling. This significantly shortens the membrane's lifespan and increases wastewater treatment costs. Summary of the Invention

[0005] In view of this, the present invention provides a method for preparing a hydrophobic polyvinylidene fluoride microporous filter membrane. The present invention mainly solves the technical problem that when polyvinylidene fluoride filter membranes are used to treat oily and high-salt wastewater, the membranes are easily fouled by organic pollutants such as oil and dirt, resulting in low pure water flux and shortened membrane life.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] A method for preparing hydrophobic polyvinylidene fluoride microporous filter membranes includes the following steps:

[0008] ① First, polyvinylidene fluoride and polyvinyl chloride are vacuum dried at 60°C for 24 hours to obtain polyvinylidene fluoride powder and polyvinyl chloride powder respectively, for later use;

[0009] ② Mix and dissolve the dry powder of polyvinylidene fluoride, polyvinyl chloride powder, and poly(m-phenylene isophthalamide) in an organic solvent, heat to 50-60℃, mechanically stir for 2-4 hours, cool to 35-40℃, add fluorinated resin, continue mechanical stirring for 1-2 hours, let stand or vacuum degas until no residual bubbles are left, and the casting adhesive is obtained.

[0010] ③ Fix the pretreated polyester fiber nonwoven fabric onto a glass plate, then uniformly coat the above casting adhesive onto its surface with a coating thickness of 0.1-0.4 mm, dry at 80-100℃ for 10-15 min, and bake at 160-180℃ for 3-5 min to obtain a hydrophobic filter membrane.

[0011] ④ Mix ZIF-8 nanoparticles and sulfobetaine methacrylate evenly, sonicate at room temperature for 10-15 minutes, place in a reaction vessel, irradiate with ultraviolet light and stir continuously with magnetic force, then let stand and cool to room temperature, degas three times with nitrogen, dilute with organic solvent, centrifuge, take the supernatant, add anhydrous methanol, let stand to obtain precipitate, the precipitate is the grafted polymer.

[0012] ⑤ Disperse the grafted polymer in an organic solvent, sonicate for 10-15 min, then oscillate at 250-300 rpm for 20-30 min. Spin the oscillated mixture onto the surface of the hydrophobic filter membrane using a needleless electrospinning machine to form a dirt-resistant nanofiber layer. Then vacuum dry for 10-12 h to obtain the hydrophobic polyvinylidene fluoride microporous filter membrane of the present invention.

[0013] In an embodiment of the present invention, the organic solvent is one or a combination of at least two of tetrahydrofuran, acetone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-N-morpholine oxide, N-methylpyrrolidone, and dimethyl sulfoxide.

[0014] In an embodiment of the present invention, the ultraviolet lamp has a power of 3 kW and an irradiation time of 30-60 s.

[0015] In an embodiment of the present invention, the electrospinning voltage in step ⑤ is 23-70kV, the receiving distance is 15-35cm, the ambient temperature for electrospinning is 25-30℃, and the humidity is 40%-70%.

[0016] In an embodiment of the present invention, the pretreatment method for polyester fiber nonwoven fabric in step ③ is as follows: uniformly coat the polyester fiber nonwoven fabric with epoxy resin adhesive, uniformly spread excess inorganic particles on it, cure at 100°C for 1 hour, bake at 150°C for 10 minutes, and then remove the excess unfixed inorganic particles to obtain the final product.

[0017] More preferably, the inorganic particles are one of porous activated carbon, silicon carbide, and porous graphite.

[0018] More preferably, the inorganic particles have an average particle size of 2.7-6 μm.

[0019] In an embodiment of the present invention, the weight parts of each component in the casting adhesive are as follows: 15-30 parts of dried polyvinylidene fluoride powder, 1-3 parts of polyvinyl chloride, 1-10 parts of poly(m-phenylene isophthalamide), 1.5-3 parts of fluorinated resin, and an appropriate amount of organic solvent.

[0020] In an embodiment of the present invention, the mass ratio of ZIF-8 nanoparticles to sulfobetaine methacrylate is 1:2.

[0021] In an embodiment of the present invention, the polyester fiber nonwoven fabric has a thickness of 0.1-0.2 mm and an average pore size of 15-25 μm.

[0022] The beneficial effects of this invention are:

[0023] 1. As can be seen from the above technical solution, compared with the prior art, the present invention uses polyvinylidene fluoride as the main component, and adds a hydrophobic filter membrane prepared by polyvinyl chloride and polyisophthaloylm-phenylenediamine as a hydrophobic layer without changing the membrane's essential nature. Then, MOF particles and sulfobetaine methacrylate are grafted onto the filter membrane surface to form a graft polymer, and a nanofiber layer is prepared by electrospinning. The hydrophobic layer and the nanofiber layer are combined to form a microporous filter membrane with a hydrophilic / hydrophobic complex structure, which not only significantly improves the separation efficiency of oily and high-salt wastewater, but also has excellent fouling resistance and mechanical strength, extending the membrane's service life.

[0024] 2. When the filter membrane prepared by the present invention is used to treat oily and high-salt wastewater, the hydrophilic nanolayer on the surface of the filter membrane can effectively shield organic pollutants such as oil stains, so that the second layer (hydrophobic filter membrane) for separating salt solution can better retain salt, improve the salt retention rate, and increase the pure water flux of the membrane. Detailed Implementation

[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] This invention discloses a hydrophobic polyvinylidene fluoride microporous filter membrane, and the specific preparation method includes the following steps:

[0027] ① First, polyvinylidene fluoride and polyvinyl chloride are vacuum dried at 60°C for 24 hours to obtain polyvinylidene fluoride powder and polyvinyl chloride powder respectively, for later use;

[0028] ② Mix and dissolve the dried polyvinylidene fluoride powder, polyvinyl chloride powder, and poly(m-phenylene isophthalamide) in a mixed solvent of N,N-dimethylacetamide and acetone (V... DMAc V 丙酮 In a mixture of 3:1, the temperature is raised to 50-60℃ and mechanically stirred for 2-4 hours. The temperature is then lowered to 35-40℃, fluorinated resin is added, and mechanical stirring continues for another 1-2 hours. The mixture is then allowed to stand or degassed under vacuum until no residual bubbles remain, thus obtaining the casting adhesive. During this process, the addition of fluorinated resin reduces the surface energy of the hydrophobic filter membrane, facilitating the hydrophobic modification of polyvinylidene fluoride and increasing the water contact angle. The addition of polyvinyl chloride will undergo a cross-linking reaction with polyvinylidene fluoride, forming a dense network on the surface of the prepared hydrophobic filter membrane, which greatly increases the salt rejection rate. Poly(m-phenylene isophthalamide) enhances the mechanical properties and hydrophobicity of the hydrophobic filter membrane.

[0029] ③ Coat the polyester fiber nonwoven fabric evenly with epoxy resin adhesive, and then evenly spread excess inorganic particles on top. These inorganic particles can be one of porous activated carbon, silicon carbide, or porous graphite, with an average particle size of 2.7-6 μm. Then, cure at 100℃ for 1 hour, bake at 150℃ for 10 minutes, remove any excess unbonded inorganic particles, and then fix the treated polyurethane fiber fabric onto a glass plate. The thickness of the polyester fiber nonwoven fabric here is 0.1-0.2 mm. The average pore size is 15-25 μm; then the above casting adhesive is uniformly coated on its surface with a coating thickness of 0.1-0.4 mm, dried at 80-100℃ for 10-15 min, and baked at 160-180℃ for 3-5 min to obtain a hydrophobic filter membrane; in this process, inorganic particles are adhered to the surface of polyurethane nonwoven fabric by adhesive. According to the "lotus effect", when the casting adhesive is coated on its surface, the roughness of the surface of the hydrophobic filter membrane is increased without adding pore-forming agents, which further improves the hydrophobicity of the prepared membrane.

[0030] ④ Mix ZIF-8 nanoparticles and sulfobetaine methacrylate at a mass ratio of 1:2 until homogeneous. Sonicate at room temperature for 10-15 minutes, place in a reaction vessel, irradiate with a 3kW UV lamp for 30-60 seconds while continuously stirring magnetically. Allow to cool to room temperature, then degas three times with nitrogen. Use a mixed solvent of tetrahydrofuran and N,N-dimethylformamide (V... THF / V DMF =1:1) dilute, centrifuge, take the supernatant, add anhydrous methanol, let stand to obtain precipitate, the precipitate is the grafted polymer;

[0031] ⑤ Add the grafted polymer to a mixed solvent of tetrahydrofuran and N,N-dimethylformamide (V THF / V DMF In a 1:1 ratio, the mixture is ultrasonically treated for 10-15 minutes, then oscillated at 250-300 rpm for 20-30 minutes. The oscillated mixture is then passed through a needleless electrospinning machine. The electrospinning voltage is 23-70 kV, the receiving distance is 15-35 cm, the ambient temperature for electrospinning is 25-30℃, and the humidity is 40%-70%. The mixture is then spun onto the surface of a hydrophobic filter membrane to form a dirt-resistant nanofiber layer. After vacuum drying for 10-12 hours, the hydrophobic polyvinylidene fluoride microporous filter membrane of this invention is obtained. In this process, on the one hand, compared with the existing technology of directly adding MOF particles, the present invention grafts MOF particles (ZIF-8 nanoparticles) and sulfobetaine methacrylate through ultraviolet light irradiation, forming a graft polymer, which solves the technical problem that direct addition of MOF particles will cause particle agglomeration. On the other hand, MOF particles have abundant pores, and sulfobetaine methacrylate is introduced into the MOF particle channels through grafting. Sulfobetaine methacrylate contains sulfonic acid groups and quaternary ammonium salt groups, which are easy to form bonds with water molecules, increasing membrane flux. At the same time, while improving water permeability, it better repels organic matter and plays an antifouling role.

[0032] The present invention will be further described below with reference to specific embodiments.

[0033] The pretreatment steps for polyurethane nonwoven fabric in the following examples and comparative examples are as follows: Polyester fiber nonwoven fabric is uniformly coated with epoxy resin adhesive, and excess inorganic particles are uniformly spread on it. These inorganic particles can be one of porous activated carbon, silicon carbide, or porous graphite, with the particle size controlled to be 2.7-6 μm. Then, it is cured at 100°C for 1 hour, baked at 150°C for 10 minutes, and the excess unfixed inorganic particles are removed to obtain the final product.

[0034] Example 1

[0035] A method for preparing hydrophobic polyvinylidene fluoride microporous filter membranes includes the following steps:

[0036] ① First, polyvinylidene fluoride and polyvinyl chloride are vacuum dried at 60°C for 24 hours to obtain polyvinylidene fluoride powder and polyvinyl chloride powder respectively, for later use;

[0037] ② Mix 15 parts by weight of polyvinylidene fluoride powder, 1 part by weight of polyvinyl chloride powder, and 1 part by weight of poly(m-phenylene isophthalamide) in an organic solvent, heat to 50°C, and mechanically stir for 2 hours. Cool to 35°C, add 1.5 parts by weight of fluorinated resin, and continue mechanical stirring for 1 hour. Let stand or degas under vacuum until no residual bubbles remain to obtain the casting adhesive; ③ Fix the pretreated polyester fiber nonwoven fabric with an average pore size of 15 μm and a thickness of 0.1 mm onto a glass plate, and then uniformly coat the above casting adhesive. The coating is applied to its surface with a thickness of 0.1 mm, dried at 80℃ for 10 min, and baked at 160℃ for 3 min to obtain a hydrophobic filter membrane; ④ ZIF-8 nanoparticles and sulfobetaine methacrylate are mixed evenly at a mass ratio of 1:2, ultrasonically treated at room temperature for 10 min, placed in a reaction vessel, irradiated with a 3 kW UV lamp for 30-60 s, and continuously magnetically stirred. The mixture is then allowed to cool to room temperature, degassed three times with nitrogen, and then treated with a mixed solvent of tetrahydrofuran and N,N-dimethylformamide (V... THF / V DMF =1:1) dilute, centrifuge, take the supernatant and add anhydrous methanol, let stand to obtain a precipitate, the precipitate is the grafted polymer; ⑤ add the grafted polymer to a mixed solvent of tetrahydrofuran and N,N-dimethylformamide (V THF / V DMF In a 1:1 ratio, the mixture is ultrasonically treated for 10 minutes, then oscillated at 250 rpm for 20 minutes. The oscillated mixture is then passed through a needleless electrospinning machine. The electrospinning voltage is 23 kV, the receiving distance is 15 cm, the ambient temperature for electrospinning is 25 °C, and the humidity is 40%. The mixture is then spun onto the surface of a hydrophobic filter membrane to form a dirt-resistant nanofiber layer. After vacuum drying for 10-12 hours, the hydrophobic polyvinylidene fluoride microporous filter membrane of this invention is obtained.

[0038] Under operating conditions of 25℃ and 0.1MPa, the mechanical strength is 11.03MPa; the flux recovery rate after 1 hour of contamination with 10g / L high-concentration bovine serum albumin solution is 63%; the flux recovery rate after contamination with 3% soybean oil is 76%; and the membrane pure water flux is 893L / m³. 2 ·h.

[0039] Example 2

[0040] A method for preparing hydrophobic polyvinylidene fluoride microporous filter membranes includes the following steps:

[0041] ① First, polyvinylidene fluoride and polyvinyl chloride are vacuum dried at 60°C for 24 hours to obtain polyvinylidene fluoride powder and polyvinyl chloride powder respectively, for later use;

[0042] ② Mix 30 parts by weight of polyvinylidene fluoride powder, 3 parts by weight of polyvinyl chloride powder, and 10 parts by weight of poly(m-phenylene isophthalamide) in an organic solvent, heat to 60°C, mechanically stir for 4 hours, cool to 40°C, add 3 parts by weight of fluorinated resin, and continue mechanical stirring for 2 hours. Let stand or degas under vacuum until no residual bubbles remain to obtain the casting adhesive; ③ Fix the pretreated polyester fiber nonwoven fabric with an average pore size of 25 μm and a thickness of 0.2 mm onto a glass plate, and then uniformly apply the above casting adhesive. The coating is applied to its surface with a thickness of 0.4 mm, dried at 100℃ for 15 min, and baked at 180℃ for 5 min to obtain a hydrophobic filter membrane; ④ ZIF-8 nanoparticles and sulfobetaine methacrylate are mixed evenly at a mass ratio of 1:2, ultrasonically treated at room temperature for 15 min, placed in a reaction vessel, irradiated with a 3 kW ultraviolet lamp for 60 s, and continuously magnetically stirred. The mixture is then allowed to cool to room temperature, degassed three times with nitrogen, and then treated with a mixed solvent of tetrahydrofuran and N,N-dimethylformamide (V... THF / V DMF =1:1) dilute, centrifuge, take the supernatant and add anhydrous methanol, let stand to obtain a precipitate, the precipitate is the grafted polymer; ⑤ add the grafted polymer to a mixed solvent of tetrahydrofuran and N,N-dimethylformamide (V THF / V DMF In a 1:1 ratio, the mixture is ultrasonically treated for 15 minutes, then oscillated at 300 rpm for 30 minutes. The oscillated mixture is then passed through a needleless electrospinning machine. The electrospinning voltage is 70 kV, the receiving distance is 35 cm, the ambient temperature for electrospinning is 30 °C, and the humidity is 70%. The mixture is then spun onto the surface of a hydrophobic filter membrane to form a dirt-resistant nanofiber layer. After vacuum drying for 12 hours, the hydrophobic polyvinylidene fluoride microporous filter membrane of this invention is obtained.

[0043] Under operating conditions of 25℃ and 0.1MPa, the mechanical strength is 10.95MPa; the flux recovery rate after 1 hour of contamination with 10g / L high-concentration bovine serum albumin solution is 61%; the flux recovery rate after contamination with 3% soybean oil is 74%; and the membrane pure water flux is 885L / m³. 2 ·h.

[0044] Example 3

[0045] A method for preparing hydrophobic polyvinylidene fluoride microporous filter membranes includes the following steps:

[0046] ① First, vacuum dry polyvinylidene fluoride (PVDF) and polyvinyl chloride (PVC) at 60℃ for 24 hours to obtain PVDF powder and PVC powder respectively, for later use; ② Mix 25 parts by weight of PVDF powder, 2 parts by weight of PVC powder, and 7 parts by weight of poly(m-phenylene isophthalamide) in an organic solvent, heat to 55℃, mechanically stir for 3 hours, cool to 38℃, add 2.5 parts by weight of fluorinated resin, and continue mechanical stirring for 1.5 hours. Let stand or degas under vacuum until no residual bubbles remain to obtain the casting adhesive; ③ The pretreated film has an average pore size of 20 μm and a thickness of 0.15 μm. A nonwoven polyester fiber of m is fixed on a glass plate, and then the above casting adhesive is uniformly coated on its surface with a coating thickness of 0.3 mm. It is dried at 90℃ for 12 min and baked at 170℃ for 4 min to obtain a hydrophobic filter membrane; ④ ZIF-8 nanoparticles and sulfobetaine methacrylate are mixed evenly at a mass ratio of 1:2, ultrasonically treated at room temperature for 13 min, placed in a reaction vessel, irradiated with a 3 kW ultraviolet lamp for 50 s, and continuously magnetically stirred. It is then allowed to stand and cool to room temperature, and degassed three times with nitrogen. A mixed solvent of tetrahydrofuran and N,N-dimethylformamide (V THF / V DMF =1:1) dilute, centrifuge, take the supernatant and add anhydrous methanol, let stand to obtain a precipitate, the precipitate is the grafted polymer; ⑤ add the grafted polymer to a mixed solvent of tetrahydrofuran and N,N-dimethylformamide (V THF / V DMF In a 1:1 ratio, the mixture is ultrasonically treated for 13 minutes, then oscillated at 300 rpm for 25 minutes. The oscillated mixture is then passed through a needleless electrospinning machine with a spinning voltage of 50 kV, a receiving distance of 20 cm, an ambient temperature of 28°C, and a humidity of 60%. The mixture is then spun onto the surface of a hydrophobic filter membrane to form a dirt-resistant nanofiber layer. After vacuum drying for 11 hours, the hydrophobic polyvinylidene fluoride microporous filter membrane of this invention is obtained.

[0047] Under operating conditions of 25℃ and 0.1MPa, the mechanical strength is 11.18MPa; the flux recovery rate after 1 hour of contamination with 10g / L high-concentration bovine serum albumin solution is 68%; the flux recovery rate after contamination with 3% soybean oil is 78%; and the membrane pure water flux is 912L / m³. 2 ·h.

[0048] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.

[0049] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

[0050] Comparative Example 1

[0051] A method for preparing a polyvinylidene fluoride microporous filter membrane includes the following steps:

[0052] ① First, vacuum dry polyvinylidene fluoride (PVDF) at 60°C for 24 hours to obtain PVDF powder; ② Dissolve 25 parts by weight of PVDF powder in an organic solvent, heat to 55°C, mechanically stir for 3 hours, cool to 38°C, add 2.5 parts by weight of fluorinated resin, and continue mechanical stirring for 1.5 hours. Let stand or degas under vacuum until no residual bubbles remain to obtain the casting adhesive; ③ Fix the pretreated polyester fiber nonwoven fabric onto a glass plate, then uniformly coat the surface of the casting adhesive with a coating thickness of 0.3 mm, dry at 90°C for 12 minutes, and bake at 170°C for 4 minutes to obtain a PVDF microporous filter membrane.

[0053] Under operating conditions of 25℃ and 0.1MPa, with a mechanical strength of 4.1MPa, the flux recovery rate after 1 hour of contamination with a 10g / L high-concentration bovine serum albumin solution was 18%; after contamination with 3% soybean oil, the flux recovery rate was 15%; and the membrane pure water flux was 523L / m³. 2 ·h.

[0054] Comparative Example 2

[0055] A method for preparing a polyvinylidene fluoride (PVDF) microporous filter membrane includes the following steps: ① First, PVDF and polyvinyl chloride are vacuum dried at 60°C for 24 hours to obtain PVDF powder and polyvinyl chloride powder, respectively, for later use; ② 25 parts by weight of PVDF powder, 2 parts by weight of polyvinyl chloride powder, and 7 parts by weight of poly(m-phenylene isophthalamide) are mixed and dissolved in an organic solvent, heated to 55°C, mechanically stirred for 3 hours, cooled to 38°C, and 2.5 parts by weight of fluorinated resin are added, and mechanical stirring is continued for 1.5 hours. The mixture is allowed to stand or vacuum degassed until no residual bubbles remain, thus obtaining the casting adhesive; ③ The pretreated polyester fiber nonwoven fabric is fixed on a glass plate, and then the above casting adhesive is uniformly coated on its surface with a coating thickness of 0.3 mm. The coating is dried at 90°C for 12 minutes and baked at 170°C for 4 minutes to obtain the final product.

[0056] Under operating conditions of 25℃ and 0.1MPa, the mechanical strength was 11.16MPa. The flux recovery rate after 1 hour of contamination with a 10g / L high-concentration bovine serum albumin solution was 21%; the flux recovery rate after contamination with 3% soybean oil was 25%; and the membrane pure water flux was 523L / m³. 2 ·h.

[0057] Comparative Example 3

[0058] A method for preparing a polyvinylidene fluoride (PVDF) microporous filter membrane includes the following steps: ① First, PVDF and polyvinyl chloride are vacuum dried at 60°C for 24 hours to obtain PVDF powder and polyvinyl chloride powder, respectively, for later use; ② 25 parts by weight of PVDF powder and 2 parts by weight of polyvinyl chloride powder are mixed and dissolved in an organic solvent, heated to 55°C, mechanically stirred for 3 hours, cooled to 38°C, and 2.5 parts by weight of fluorinated resin are added, and mechanical stirring is continued for 1.5 hours. The mixture is allowed to stand or vacuum degassed until no residual bubbles remain, thus obtaining the casting adhesive; ③ The pretreated polyester fiber nonwoven fabric is fixed on a glass plate, and then the above casting adhesive is uniformly coated on its surface with a coating thickness of 0.3 mm. The coating is dried at 90°C for 12 minutes and baked at 170°C for 4 minutes to obtain the final product.

[0059] Under operating conditions of 25℃ and 0.1MPa, with a mechanical strength of 7.3MPa, the flux recovery rate after 1 hour of contamination with a 10g / L high-concentration bovine serum albumin solution was 20.5%; the flux recovery rate after contamination with 3% soybean oil was 23%; and the membrane pure water flux was 517L / m³. 2 ·h.

Claims

1. A method for preparing a hydrophobic polyvinylidene fluoride microporous filter membrane, characterized in that, Includes the following steps: ① First, polyvinylidene fluoride and polyvinyl chloride are vacuum dried at 60°C for 24 hours to obtain polyvinylidene fluoride powder and polyvinyl chloride powder respectively, for later use; ② Mix and dissolve the dry powder of polyvinylidene fluoride, polyvinyl chloride powder, and poly(m-phenylene isophthalamide) in an organic solvent, heat to 50-60℃, mechanically stir for 2-4 hours, cool to 35-40℃, add fluorinated resin, continue mechanical stirring for 1-2 hours, let stand or degas under vacuum until no residual bubbles are left, and the casting adhesive is obtained. ③ Fix the pretreated polyester fiber nonwoven fabric onto a glass plate, then uniformly coat the above casting adhesive onto its surface with a coating thickness of 0.1-0.4 mm, dry at 80-100℃ for 10-15 min, and bake at 160-180℃ for 3-5 min to obtain a hydrophobic filter membrane. ④ Mix ZIF-8 nanoparticles and sulfobetaine methacrylate evenly, sonicate at room temperature for 10-15 minutes, place in a reaction vessel, irradiate with ultraviolet light and stir continuously with magnetic force, then let stand and cool to room temperature, degas three times with nitrogen, dilute with organic solvent, centrifuge, take the supernatant, add anhydrous methanol, let stand to obtain precipitate, the precipitate is the grafted polymer. ⑤ Disperse the grafted polymer in an organic solvent, sonicate for 10-15 min, then oscillate at 250-300 rpm for 20-30 min. Spin the oscillated mixture onto the surface of the hydrophobic filter membrane using a needleless electrospinning machine to form a dirt-resistant nanofiber layer. Then vacuum dry for 10-12 h to obtain the hydrophobic polyvinylidene fluoride microporous filter membrane of the present invention.

2. The method for preparing a hydrophobic polyvinylidene fluoride microporous filter membrane according to claim 1, characterized in that, The organic solvent is one or a combination of at least two of the following: tetrahydrofuran, acetone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-N-morpholine, N-methylpyrrolidone, and dimethyl sulfoxide.

3. The method for preparing a hydrophobic polyvinylidene fluoride microporous filter membrane according to claim 1, characterized in that, In step ④, the ultraviolet lamp has a power of 3 kW and an irradiation time of 30-60 seconds.

4. The method for preparing a hydrophobic polyvinylidene fluoride microporous filter membrane according to claim 1, characterized in that, In step ⑤, the electrospinning voltage is 23-70kV, the receiving distance is 15-35cm, the ambient temperature for electrospinning is 25-30℃, and the humidity is 40%-70%.

5. The method for preparing a hydrophobic polyvinylidene fluoride microporous filter membrane according to claim 1, characterized in that, The pretreatment method for polyester fiber nonwoven fabric in step ③ is as follows: uniformly coat the polyester fiber nonwoven fabric with epoxy resin adhesive, evenly spread the excess inorganic particles on it, cure at 100℃ for 1 hour, bake at 150℃ for 10 minutes, and then remove the excess unfixed inorganic particles to obtain the final product.

6. The method for preparing a hydrophobic polyvinylidene fluoride microporous filter membrane according to claim 5, characterized in that, The inorganic particles are one of porous activated carbon, silicon carbide, and porous graphite; the average particle size of the inorganic particles is 2.7-6 μm.

7. The method for preparing a hydrophobic polyvinylidene fluoride microporous filter membrane according to claim 1, characterized in that, The casting adhesive contains the following components in parts by weight: 15-30 parts of dried polyvinylidene fluoride powder, 1-3 parts of polyvinyl chloride, 1-10 parts of poly(m-phenylene isophthalamide), 1.5-3 parts of fluorinated resin, and an appropriate amount of organic solvent.

8. The method for preparing a hydrophobic polyvinylidene fluoride microporous filter membrane according to claim 1, characterized in that, The ZIF-8 nanoparticles and sulfobetaine methacrylate are in a mass ratio of 1:

2.

9. The method for preparing a hydrophobic polyvinylidene fluoride microporous filter membrane according to claim 1, characterized in that, The polyester fiber nonwoven fabric has a thickness of 0.1-0.2 mm and an average pore size of 15-25 μm.

Citation Information

Patent Citations

  • Anti-fouling hydrophilic PVDF modified membrane and preparation method thereof

    CN108310984A

  • Preparation method of composite catalytic material for efficiently degrading farm chemical wastewater

    CN113908871A